Synthesis and hydrophobic modification of silica-CNT hybrid aerogels via one-pot and sol-gel methods using sustainable precursor - Yapici, Emine; Kececi, Berat; Yucel, Sevil (SPRINGER, 2025)
Silica-CNT hybrid aerogels (SCHAs) were fabricated using both one-pot synthesis (OPS) and conventional sol-gel methods. Following gelation, the samples were dried using two different techniques: ambient pressure drying (APD) and supercritical CO2 drying (SCD). Sustainable sodium silicate precursor was used. The gels were surface modified with trimethylchlorosilane (TMCS) and hexamethyldisilazane (HMDS), which acted as hydrophobizing silylating agents. The prepared aerogel was characterized by Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) analyzer, thermogravimetric and differential thermal analyzer (TG-DTA), Fourier transform infrared spectrometer (FT-IR), field emission scanning electron microscope (FE-SEM) and contact angle analyzer for structural, thermal, functional, surface, morphological properties. Thermal stability of SCHAs investigated by TG-DTA shows a hydrophobic nature up to 600 degrees C. FE-SEM images confirmed the mesoporous nature of aerogels. The surface area and pore size were measured to range from 133 to 535 m(2)/g and 3.55 to 9.46 nm, respectively, while the total pore volume was found to range from 0.24 to 1.39 cm(3)/g. The water contact angle (WCA) measurements affirm that most of the synthesized SCHAs exhibit excellent superhydrophobicity, with contact angles exceeding 154 degrees.
Keywords: Superhydrophobicity; Silica aerogel; Carbon nanotube (CNT); Silylating agents; Supercritical CO(2)drying (SCD); Ambient pressure drying (APD); CARBON NANOTUBE; SURFACES; ADSORPTION; COATINGS; Chemistry; Materials Science